BACTERIAL CONTAMINATION OF HANDS OF MEDICAL INTERNS AND UNDERGRADUATE STUDENTS - Senthil, Sunandha; Hegde, Ashwini; Kulkarni, Vaman; M, Radhakrishna (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Cross-transmission by the hands of health-care workers is considered the main route of spread of nosocomial infections. Awareness among medical students and interns about the importance of hand hygiene practices and facilities for its adherence can play a major role in reducing disease transmission. The objectives of the present study were: (1) To determine the level and type of microbial contamination present on the hands of medical students and interns from a teaching hospital of Mangalore, Karnataka, and (2) to evaluate the relationship between hand contamination and knowledge, attitude, and practices of hand hygiene. Methods: Swabs were obtained from the dominant hand and the skin surface beneath the rings of participants during their routine work hours. Laboratory analysis was carried out within one hour of collection of samples. The participants were asked to fill a questionnaire on hand hygiene. Descriptive statistics and analysis was done by Chi-square test. Results: Of the 70 study participants, 35 (50%) were medical undergraduate students and 35 (50%) were medical interns. The contamination rate was higher among the undergraduates (91.4% [32/35]) compared to interns (77.1% [27/35]). 38 (54%) participants hands were contaminated with Staphylococcus aureus, of which 17 (44.7%) were methicillin-resistant S. aureus. Although overall knowledge status about hand hygiene was good, concepts about certain key elements in hand hygiene were not clearly understood by the participants. Knowledge about alcohol-based hand rubs was not up to the mark. The level of knowledge was found to be similar between UGs and interns and between the genders. Wearing ring while handling patients had an influence on hand contamination. Conclusions: Although the overall knowledge about hand hygiene was good, very few participants knew that hand hygiene after exposure to immediate surroundings of patient can prevent cross-transmission. Health-care workers may unknowingly carry antibiotic-resistant bacteria on their hands. Being unaware of this fact may have serious repercussions as the students and interns may serve as a medium for the spread of nosocomial infections.